Shear amplification of orientation in Nylon 11/clay nanocomposites during melt casting and resulting electrical properties. Issue 3 (5th January 2023) - Jain, Mayank; Mutlu, Zeynep; Mao, Jiahao; Zhou, Jierui; Zhou, Peinan; Wu, Chao; Isik, Tugba; Cao, Yang; Ortalan, Volkan; Cakmak, Mukerrem
Abstract: In this study, the effect of organically modified clay on the orientation enhancement in Nylon 11 in melt casting was investigated. Nylon 11 was mixed with 1 and 3 wt% Cloisite 20A using twin screw extrusion and they were cast into films with varying take‐up speeds. The addition of clay in Nylon 11 helped increase orientation levels substantially in melt cast films, both as a function of clay concentration as well as take‐up speeds. This was primarily due to shear amplification effect caused by the movement of adjacent clay nanoparticles due to the shear flow gradient within the die. At low clay concentrations, the sub‐Tm stretchability, and electrical breakdown strength improve as the presence of clay reduces inter/intrachain hydrogen bonding. At higher clay concentrations, both orientation and electrical breakdown levels decrease. The latter is primarily caused by increased percolation path of charge carriers. Nevertheless, clay nanoplatelets were very effective in their role as melt processing aids, as they enhance orientation levels of Nylon 11 thin films by shear amplification effect where they increase local chain orientation of chains trapped between clay platelets while their orientation relaxation is suppressed. Abstract : Shear Amplification effect.